Post-operative delay in return of function following guided growth tension plating and use of corrective physical therapy. (May 2014) - Fillingham, Yale A.; Kroin, Ellen; Frank, Rachel M.; Erickson, Brandon; Hellman, Michael; Kogan, Monica
Purpose: Guided growth has long been used to treat growth deformities, but the Eight-Plate ® system has recently become more widely used by pediatric orthopaedists. Because the current literature lacks evaluation of functional status in the immediate post-operative period, we investigated functional status following use of the Eight-Plate ® system. Methods: We evaluated post-operative delay in return of function following treatment with the Eight-Plate ® system at two weeks after surgery. Fifty-one consecutive patients with a growth deformity were treated with the Eight-Plate ® system. Patients were comprised of 32 male and 19 female patients with an average age of 11 years (range 2–17.9 years). Results: Among study participants, 19 patients (37.3 %) had post-operative delay of function. The rate of delayed function for patients 10 years of age or younger and 11 years of age or older was respectively 11.8 and 50 % ( P = 0.002). Six of the 19 patients were treated with four or more plates, of which five patients (83.3 %) developed delayed return of function. The rate of delayed function in patients with at least one femoral plate compared to no femoral plate was respectively 45 and 9.1 % ( P = 0.006). Bilateral operations were associated with a 66.7 % rate of delayed function compared to 25 % with unilateral operations ( P = 0.004). When patients with delay of function were treated with physical therapy, 12 of 13 patients (92.3 %) had complete resolution of their symptoms. Conclusion: Statistical significance demonstrated that patients at the greatest risk were 11 years of age or older, with four or more plates, with femoral plates, or with bilateral operations. Patients with delayed function were readily corrected by physical therapy.